A preliminary study on the properties oil palm board: Effect of resin content / Nurrohana Ahmad … [et al.] - Ahmad, Nurrohana; Kasim, Jamaludin; Yamani, Shaikh Abdul Karim; Mohktar, Anis; Yunus, Nor Yuziah (Universiti Teknologi MARA Cawangan Pahang, 2007)
Three-layer oil palm boards were produced using urea formaldehyde resin. Face and back layer particles were sprayed with 10%, 12% and 14% resin while the core was maintained at 10% resin content. The oil palm board was hot-pressed at 165°C for 6 minutes at a pressure of 120 kgcm-2. With increasing resin content, all the mechanical and physical properties improved significantly. However, all board properties did not meet the minimum requirement of the BS 5669.